Improving the efficiency of new automatic dishwashing detergent formulation by addition of thermostable lipase, protease and amylase - Naganthran, Ashwini; Masomian, Malihe; Raja Abd. Rahman, Raja Noor Zaliha; Mohamad Ali, Mohd Shukuri; Mohd Nooh, Hisham (MDPI, 2017)
he use of T1 lipase in automatic dishwashing detergent (ADD) is well established, but efficiency in hard water is very low. A new enzymatic environmentally-friendly dishwashing was formulated to be efficient in both soft and hard water. Thermostable enzymes such as T1 lipase from Geobacillus strain T1, Rand protease from Bacillus subtilis strain Rand, and Maltogenic amylase from Geobacillussp. SK70 were produced and evaluated for an automatic dishwashing detergent formulation. The components of the new ADD were optimized for compatibility with these three enzymes. In compatibility tests of the enzymes with different components, several criteria were considered. The enzymes were mostly stable in non-ionic surfactants, especially polyhydric alcohols, Glucopon UP 600, and in a mixture of sodium carbonate and glycine (30:70) buffer at a pH of 9.25. Sodium polyacrylate and sodium citrate were used in the ADD formulation as a dispersing agent and a builder, respectively. Dishwashing performance of the formulated ADDs was evaluated in terms of percent of soil removed using the Leenert‘s Improved Detergency Tester. The results showed that the combination of different hydrolysis enzymes could improve the washing efficiency of formulated ADD compared to the commercial ADD “Finish” at 40 and 50 C.